Réponses

2013-05-06T17:01:03+02:00

Bonjour,

 

AD = AB+BC+CD, donc :

AD = AB+1+1 = AB+2, donc AD = AB-2 = 3,6-2

AD = AC+CD = AC+1, donc AC = AD-1 = 3,6-1

 

Les droites (CD) et (EG) se coupent en A et on a (GC)//(DE).

Donc, d'après le théorème de Thalès :

\frac{AC}{AD} = \frac{GC}{ED} = \frac{AG}{AE}\\ \frac{3{,}6-1}{3{,}6} = \frac{CG}{2{,}8}\\ CG = 2{,}8\times \frac{2{,}6}{3{,}6} = \frac{91}{45} \approx 2{,}02 \text{ m}

 

Les droites (DB) et (EF) se coupent en A et on a (ED)//(BF).

Donc, d'après le théorème de Thalès :

\frac{AB}{AD} = \frac{FB}{ED} = \frac{AF}{AE}\\ \frac{3{,}6-2}{3{,}6} = \frac{FB}{2{,}8}\\ FB = 2{,}8 \times \frac{1{,}6}{3{,}6} = \frac{56}{45} \approx 1{,}24 \text{ m}